The patient perspective on remote monitoring of implantable cardiac devices - Hillmann, Henrike A. K.; Hansen, Claudius; Przibille, Oliver; Duncker, David (Frontiers in Cardiovascular Medicine, 2023)
Aims: Remote monitoring for patients with cardiac implantable electronic devices (CIEDs) is well-established in clinical routine and recommended by current guidelines. Nevertheless, data regarding patients’ perception is limited. This study aims to analyze the patient perspective on remote monitoring of cardiac devices in Germany. Methods and Results: Patients with a CIED and remote monitoring of all current manufacturers from three German centers were asked to fill in a questionnaire to participate. The questionnaire consisted of 37 questions regarding the patients’ individual use and perspective on remote monitoring. Survey participation was anonymous and on a voluntary basis. 617 patients (71.6% male) participated. Most patients answered to feel well-informed (69.3%) and reported to have an unchanged or improved coping (98.8%) since start of remote monitoring. At least 39.7% experienced technical problems regarding the transmitter, whereas most patients (60.3%) answered to never note technical issues. After starting remote monitoring, patients reported a prolongation of intervals of in-person follow-up visits (p<0.001). Older patients had a significantly less interest than younger patients in using their own smartphone for data transfer (p<0.001). Conclusion: Patients with remote follow-up of CIED report that they feel well-informed about the telemedicine approach. Remote monitoring can support coping with their disease and technical problems are not frequently reported. With remote monitoring, patients experienced a prolongation of intervals of in-person follow-up visits and especially younger patients would appreciate a smartphone-based data transfer of their CIEDs.